Analysis of Class X Students' Mathematical Problem-Solving Abilities in Completing Arithmetic Sequences and Series Material - Muhammad Ikhsan Juniantika; Rika Mulyati Mustika Sari (Universitas Sebelas Maret, 2025)
This research aims to assess students' mathematical problem-solving abilities regarding arithmetic sequences and series. The research was conducted in one high school of Karawang district, where a total of 35 students were taken from a single class. From the data collected, it was found that 25 students, which accounts for 71.4%, had medium-level mathematical problem-solving abilities, while 5 students, each from the high and low categories, accounted for 14.3% respectively. The researchers selected three students as samples to analyze each indicator of their mathematical problem-solving abilities. The study results indicate that students in the low category have not achieved the indicators of planning and checking again. Students in the medium category have not reached the indicators of checking again, while students in the high category have achieved all the indicators of mathematical problem-solving ability. The average indicator score for all students in the research is 46%, which is still low.